2020
DOI: 10.3390/cells9102271
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic miRNA-Enriched Extracellular Vesicles: Current Approaches and Future Prospects

Abstract: Extracellular vesicles (EVs) are 50–300 nm vesicles secreted by eukaryotic cells. They can carry cargo (including miRNA) from the donor cell to the recipient cell. miRNAs in EVs can change the translational profile of the recipient cell and modulate cellular morphology. This endogenous mechanism has attracted the attention of the drug-delivery community in the last few years. EVs can be enriched with exogenous therapeutic miRNAs and used for treatment of diseases by targeting pathological recipient cells. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 84 publications
1
54
0
3
Order By: Relevance
“…Proteomic studies have so far identified more than 4000 different types of proteins in EVs [20]. In addition, hundreds of different messenger RNAs and micro RNAs have been identified in BM-MSCEVs [21]. Mechanisms of action of these proteins and RNAs in treating neurodegenerative diseases include the following.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies have so far identified more than 4000 different types of proteins in EVs [20]. In addition, hundreds of different messenger RNAs and micro RNAs have been identified in BM-MSCEVs [21]. Mechanisms of action of these proteins and RNAs in treating neurodegenerative diseases include the following.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of exosomes with miRNA is commonly achieved by transfecting adipose tissue-derived stem cells and mesenchymal stem cells with the miRNA of choice. The potential of the EVs as carriers of exogenous therapeutic miRNA has been discussed in detail in earlier reports [ 137 ]. MiRNA-enriched exosomes have been used in a wide variety of diseases, including brain disorders [ 138 , 139 , 140 , 141 ], cardiac diseases [ 142 , 143 , 144 ], muscular disorders [ 126 , 145 ], cancer [ 146 , 147 ] etc.…”
Section: Non-viral-based Mirna and Anti-mirna Oligonucleotide Delimentioning
confidence: 99%
“…Alternatively, it is established that increasing the concentration of iRNAs in the cytosol of the cell is concomitant with their heightened copy number in exosomes [ 152 ]. In this regard, MSCs can be manipulated to express shRNA or miRNA of interest via transfection or transduction.…”
Section: Main Textmentioning
confidence: 99%